2018
DOI: 10.3390/beverages4010015
|View full text |Cite
|
Sign up to set email alerts
|

Total Polyphenol Content and Antioxidant Capacity of Tea Bags: Comparison of Black, Green, Red Rooibos, Chamomile and Peppermint over Different Steep Times

Abstract: Globally, traditional and herbal teas are a prominent dietary source of polyphenols, and represent a class of bioactive molecules that are closely associated with a variety of health benefits. Most consumers prepare tea using tea bags, although there is little information about whether this production step alters the content of the final product. The study purpose was to investigate the effect of steep time and tea type on the polyphenol content and predicted antioxidant capacity of commercially available tea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 18 publications
2
30
0
3
Order By: Relevance
“…TPC was measured with Folin-Ciocalteau's methodology (ISO 14502-1:2005) with a gallic acid standard to determine GAE. [12][13][14] Differing concentrations of BT according to TPC were measured at 0.1, 0.5, 0.75, 1, 2, 5, and 10 lg GAE/mL. Concentrations of 0.1-1 lg GAE/mL are likely relatable to consuming two to three cups of BT per day.…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…TPC was measured with Folin-Ciocalteau's methodology (ISO 14502-1:2005) with a gallic acid standard to determine GAE. [12][13][14] Differing concentrations of BT according to TPC were measured at 0.1, 0.5, 0.75, 1, 2, 5, and 10 lg GAE/mL. Concentrations of 0.1-1 lg GAE/mL are likely relatable to consuming two to three cups of BT per day.…”
Section: Methods Results and Discussionmentioning
confidence: 99%
“…Although it has been demonstrated that most of the phenolic compounds (80-90%) are released in the first five minutes, the release time varies among teas. For example, most of the phenolic compounds in green tea are released in the first 2-3 min (Cleverdon et al, 2018). However, our results show clearly that, even after infusion, the residues still contain a large quantity of TPC and AC, and the availability of TPC increases in all of the evaluated materials, making it feasible to reuse the residues for another infusion.…”
Section: Residuesmentioning
confidence: 73%
“…Worldwide, the infusions are an important source of phenolic compounds, and represent a class of bioactive molecules that are closely associated with a variety of health benefits (Cleverdon et al, 2018). Dur results for TPC in infusions coincide with Gorjanović et al (2012), who also report that black tea is that with the highest TPC.…”
Section: Infusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest total concentration of flavonoid compounds (69.57 ± 0.8 mg 100 g -1 ) was found in the Yarrow herbal tea infusion. Scientists (from Brock University, Canada) Cleverdon et al (2018) reported that the Peppermint tea had the highest antioxidant capacity when testing across the bagged tea [18].…”
Section: Resultsmentioning
confidence: 99%